SYLLABUS DESIGN FOR ENGLISH COURSES - Irfani, Bambang (English Education: Jurnal Tadris Bahasa Inggris, 2014)
The planning of courses including designing curriculum and syllabus is often ignored in English language teaching and teacher training.  Harmer (2000) states that decisions about course content are very often not taken by teachers, but by some higher authority.  Even many institutions present the syllabus in terms of the main textbook to be used - by a certain date, teachers are expected to have covered a certain number of units in the book.  At the same time teachers are often provided with a list of supplementary material and activities available. Yet, the graduates of such programs as English teacher training are often required to carry out course design task without having received sufficient training to do so.  As a matter of fact, course design requires specialized expertise which can be gained through learning and practice.  Designing courses is unlike preparing one's own teaching as it should be understood by others who will use the design.  Therefore, it is very urgent to equip the English teachers with the basic competence of course design.